The content of carotenoids in the fruits of sea buckthorn in the forest-steppe zone of Altai Krai - I. A. Kondrateva; I. D. Borodulina; Y. A. Zubarev (Проблемы ботаники Южной Сибири и Монголии, 2020)
The paper presents the results of a quantitative study of carotenoids in the fruits of sea buckthorn in 2018.The range of variability of feature with its degree of variation is revealed. Hybrids with high carotenoid content wereidentified. A correlation analysis was performed to determine the value of connection between the number of carotenoidsand the hydrothermal coefficient of the growing season.